Silicon/LiNi0·8Co0·15Al0·05O2 lithium-ion pouch cells charging and discharging at −40 °C temperature. (10th September 2020) - Subburaj, T.; Brevet, W.; Farmakis, F.; Tsiplakides, D.; Balomenou, S.; Strataki, N.; Elmasides, C.; Samaniego, B.; Nestoridi, M.
Abstract: Though Li-ion batteries offer excellent performance at room temperature, their operation at subzero temperatures is restricted by the capacity and the poor cycling performance due to sluggish kinetics. To this end, we have prepared 1 Ah pouch cells composed of high specific capacity silicon (Si) anode, LiNi0·8 Co0·15 Al0·05 O2 (NCA) cathode and low temperature electrolyte and have demonstrated their performance at 20 °C and −40 °C. At −40 °C, Si/NCA pouch cells deliver >700 mAh of discharge capacity (ca. 65% compared to 20 °C) after being charged at the same low temperature without any external heating support. Regarding cycling performance, at 20 °C, after 100 cycles, Si/NCA pouch cells lose around 20% of their initial discharge capacity, whereas at −40 °C, they retain 50% of the initial capacity after 60 charging/discharging cycles at the same temperature. Results indicate that degradation mechanisms of the Si/NCA system when cycled at −40 °C are more severe than when cycled at 20 °C. By analyzing differential capacity and voltage profiles, the capacity degradation at −40 °C is found to be related to the absence of one characteristic redox pair around 4 V. Post-mortem X-ray diffraction (XRD) investigation on the NCA cathodes reveals significant structural transformations, more pronounced when cycling at −40 °C, which are responsible for the capacity loss.